Resilience in Russian youth. Issue 2 (2nd April 2016) - Makhnach, Alexander V.
Abstract : In this paper, the results of testing on the Russian national sample with the Child and Youth Resilience Measure, developed in the framework of the International Resilience Project (Ungar et al., 2008. The study of youth resilience across cultures: Lessons from a pilot study of measurement development. Research in Human Development, 5, 166–180), are presented. Resilience of young Russian people (students of the senior classes of high school who successfully socialise; students of a special school for pupils with emotional and behavioural difficulties, who come into conflict with the law, family or community; orphan adolescents living in state-run orphanages; and first-year Psychology students) is described in a dimension of such factors as 'relationships', 'culture', 'personality traits' and 'community'. Some specifics and differences of the four groups are discussed.